Editorial review: Lesson study as curriculum analysis (Kyouzai Kenkyuu) in action and the role of "the teacher as a researcher". Issue 1 (3rd January 2017) - Elliott, John
Abstract : Purpose: The purpose of this paper is to discern and discuss links and connections between the ideas and insights contained in the articles published in Issue 6.2, in a way which portrays the key features of lesson study in an international context, its conceptual relationship with the ideas of Lawrence Stenhouse, and its analytic potential to effect pedagogical transformation in a global context. Design/methodology/approach: To create a basis for a fruitful discussion about the critical features of Lesson and Learning Studies as it globalises between readers and the authors of the eight texts published, three of which are authored by practicing school teachers. Findings: The author pinpoints four critical implementation issues that should provide a focus for further deliberation about how to realise the potential of lesson and learning studies for improving the quality of teaching and learning in educational institutions. These are: developing methods of analysis that disrupt and challenge the cultural scripts that shape teaching and learning in educational institutions; developing conditions and support systems that enable teachers not only to develop their practice through lesson and learning study, but also to participate in the development of theories that can powerfully inform such study; creating sustainable programmes of high-quality lesson and learning studies in educational institutions when they may stand in a state of tension with the prevailing organisational culture; and exploring the potential of creative methodological mixes, using both qualitative and quantitative research methods, for improving the quality of teaching and learning through lesson and learning study. Originality/value: This editorial review provides a criterial framework for evaluating the quality of programmes of lesson and learning studies in educational institutions.